1999
DOI: 10.1097/00004728-199905000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Solitary Fibrous Tumor: A Clinicopathological Case Study

Abstract: We present a case of extrapleural solitary fibrous tumor arising within the muscle, an unusual and hitherto-undescribed tumor lesion. A 42-year-old woman presented a painless mass in her left thigh. The lesion was depicted as an intramuscular mass that enhanced on both CT and MRI, showing quite rich tumor vascularity. The histological features of the tumor were spindle cell proliferation with various histological patterns, typical fibrocollagenous background, and positive immunoreactivity for CD-34.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…12 From the clinical point of view, an extrapleural SFT is usually a painless mass in the deep soft tissue without specific symptoms. 13 extrapleural SFT can show both benign and malignant behavior. From 10% to 15% of the tumors are malignant, occurring with more frequency in the cellular than in the fibrous forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 From the clinical point of view, an extrapleural SFT is usually a painless mass in the deep soft tissue without specific symptoms. 13 extrapleural SFT can show both benign and malignant behavior. From 10% to 15% of the tumors are malignant, occurring with more frequency in the cellular than in the fibrous forms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many authors reported that the majority of these tumors (80%) showed hypointense or isointense on T1-weighted image relative to muscle, and hypointense on T2-weighted image. [12][13][14][15][16][17][18][19] On the other hand, Shin JH et al 20 reported that the extrapleural SFT in the buccal space showed hyperintense on T2-weighted image. Contrast enhanced MRI shows heterogeneous in as many as 82% of extrapleural SFT cases, and homogeneous enhancement effect in approximately 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers report SFTs in the orbit [5], meninges [5], parotid and submandibular glands [6], lung [10], mediastinum [9], stomach and ileum [10], kidney [5], and skin [4,6], among other locations. SFTs are often asymptomatic, though large lesions may present with nonspecific clinical symptoms such as abdominal fullness or discomfort [8,11]. In one recent large series, extrathoracic SFTs were more commonly symptomatic (83% of cases) than were intrathoracic SFTs (23% of cases) [11].…”
Section: Case Reportmentioning
confidence: 99%
“…SFTs are often asymptomatic, though large lesions may present with nonspecific clinical symptoms such as abdominal fullness or discomfort [8,11]. In one recent large series, extrathoracic SFTs were more commonly symptomatic (83% of cases) than were intrathoracic SFTs (23% of cases) [11]. Painless masses are characteristic of more superficial SFTs [8].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation